Carcass and meat quality of red-winged tinamou (Rhynchotus rufescens) selected for muscle growth - Martins, Eduardo Henrique [UNESP]; Malheiros, Jessica Moraes; dos Santos Correia, Luiz Eduardo Cruz [UNESP]; de Moraes Vilar, Claudianny Souto Maior; de Oliveira, Matheus Henrique Vargas [UNESP]; Dominguez-Castaño, Pablo [UNESP]; de Fátima Aguiar, Édina; de Vasconcelos Silva, Josineudson Augusto Ii [UNESP] (Springer Nature, 2023)
The aim of the present study was to evaluate the efficiency of selection for body growth and its association with carcass and meat quality traits in the red-winged tinamou. Two experimental groups were selected based on the selection index: selection group with a higher index (TinamouS) and commercial group with a lower index (TinamouC). Weight at 180 days and slaughter weight were significantly higher (p < 0.05) in the TinamouS group, as were hot carcass weight, skinless breast weight, wing weight, and thigh and drumstick weight. The meat quality traits or sensory attributes did not differ significantly (p > 0.05) between groups. A significant positive correlation (0.59; p < 0.05) was found between shear force and chewability and a significant negative correlation (− 0.59; p < 0.05) between aroma intensity and strange aroma. The present study suggests that the selection index promotes greater body growth and preserves meat quality and sensory traits in red-winged tinamou.
Keywords: Meat tenderness; Selection index; Sensory analysis; Tinamidae